Quantifying Sentence Variety in English Learners - Charpentier-Jiménez, William (2020)
This article studies students’ use of sentence variety in an ESL writing course. The study includes three sentence features: (a) sentence types, (b) sentence combining, and (c) sentence patterns. Although sentence variety is part of the curriculum, the actual use of sentence structures has not been measured so far. By understanding students’ use of sentence structures, it is possible to propose valid curricular changes in the language program. This quantitative project has been carried out by analyzing 36 paragraphs written by students in the first writing course of a B.A. in English. The study included 433 sentences. Each sentence was examined individually. Data shows that 14.54% of the sentences presented a type of error. The types of errors included were the following: 12 fragments (2.77%), 29 fused sentences (6.69%), and 22 comma splices (5.08%). The remaining number of traditional sentences studied was 370 (85.45%). Results demonstrate that students favor certain types of structures and ignore others. Therefore, the demands of the curriculum and the written production of students lack coherence. Consequently, curricular changes must be incorporated to improve students’ written production.